Análise tribológica de conjugados (CrAl)N depositados por PAPVD sobre ferramentas de metal duro com diferentes rugosidades superficiais - Joao Luiz Turchetti Lara Rezende (2010)
Hardmetal coated with CrAlN is a useful tooling for high hardness materials machining. Wear and its tribological consequences when modifying the initial roughness of the substract is the subject of this paper. Hardmetal (WC 95%-Co 5%) was submitted to three different roughness by grinding and polishing. Sandpaper and polishing were used to modify surface roughness before coating. 3D perfilometry was used to measure the roughness. After coating, dry pin on disc sliding wear test were done using a silicon nitride 6mm sphere as counter part. Normal force of 40N, rotation of 500rpm, and slide distance of 3.000m were chosen for the test parameters. The wear volume was measuremed by perfilometry technique. The results showed that wear mechanism was driven by tribochemical effects (oxidation) in the specimen surface. There was not identified substantial difference wear rate for different roughness systems in sliding wear tests. The effect of the plato profile type with high density of asperities per area seems to have important role in the low wear performance. High asperities density increases adhesion and drives severe wear mechanism, observed mainly by wear powder analysis (particles size, quantity and chemical analysis), presence of sphere material in the wear track and friction load rates.